TECHNIQUES AND TACTICS IN BASKETBALL ACCORDING TO THE INTENSITY IN OFFICIAL MATCHES - José Francisco Daniel (Revista Brasileira de Medicina do Esporte)
ABSTRACT Introduction: Basketball is characterized as an intermittent sport in which currently stand out the highest intensity in which the actions occur, demanding for sport performance the optimum and homogeneous development of physical, technical, tactical, psychological and intellectual components. In this sense, the understanding of the game according to the technical and tactical actions performed and the knowledge of body’s responses are important for planning, monitoring and control of the training. Objective: The aim of this study was to describe the intensity of basketball tactical actions and the relationships between technical actions and intensity during the different game periods (GP). Methods: Ten athletes of the Brazilian male basketball elite participated in this study (27.60±5.54 years, 192.62±7.63 cm, 91.60±11.51 kg, 10.66±4.11% of body fat) in six official matches of the National Basketball League (LNB, Brazil). Anthropometric measures and motor tests were performed and tactical (defensive, offensive and transition), technical [shares number (SN) and efficiency ratio (ER)] and physical actions [percentage of lactate threshold heart rate (%HRthr)] were correlated. Spearman’s correlation coefficient was used between SN, ER and %HRthr. Results: The main results point to: (1) positive and significant relationship (except the 4th GP) between SN, ER and %HRthr; (2) tactical actions presented HR near the lactate threshold, being apparently the highest median for the transitions (107.4%HRthr). Conclusion: The game is intense, with moments of HRpeak, but the median is slightly above of HRthr, that it is where the best relationship between SN and ER occurs.